Substituted benzyloxytricyclic compounds as retinoic acid-related orphan receptor gamma t (RORγt) agonists. Issue 12 (15th June 2020) - Harikrishnan, Lalgudi S.; Gill, Patrice; Kamau, Muthoni G.; Qin, Lan-Ying; Ruan, Zheming; O'Malley, Daniel; Huynh, Tram; Stachura, Sylwia; Cavallaro, Cullen L.; Lu, Zhonghui; J.-W. Duan, James; Weigelt, Carolyn A.; et al.
Graphical abstract: Abstract: Substituted benzyloxy aryl compound 2 was identified as an RORγt agonist. Structure based drug design efforts resulted in a potent and selective tricyclic compound 19 which, when administered orally in an MC38 mouse tumor model, demonstrated a desired pharmacokinetic profile as well as a dose-dependent pharmacodynamic response. However, no perceptible efficacy was observed in this tumor model at the doses investigated.